Uji Aktivitas Antibakteri Ekstrak Etanol Kaktus Centong (Opuntia cochenillifera) Terhadap Pertumbuhan Bakteri Staphylacoccus epidermidis Dengan Media Buatan Pati Pisang Kepok (Musa paradisiaca) - Manuppak Irianto Tampubolon; Natanael Priltius; Alfian Rejekinta Munthe (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2022)
Centong Cactus (Opuntia cochenilifera) is one of the plants used to treat health problems, but this is done based on hereditary experience. This plant contains flavonoids, tannins, saponins, and steroids. The purpose of this study was to see the antibacterial activity of the ethanol extract of Centong cactus (Opuntia cochenillifera) using alternative media of Kepok banana starch and Muller Hilton Agar Media. This study was conducted experimentally. Samples were extracted by maceration method using 96% ethanol as solvent. Antibacterial activity was tested by disk diffusion method with paper backing technique. The parameters observed were zone of inhibition. Based on the result of the inhibition zone research, the best results were obtained on the banana starch media with a concentration of 40% 18,7mm and on Muller Hilton Agar media with a concentration of 40% 20,1mm. The antibacterial test result stated that the ethanolic extract of Centong cactus could provide an effective inhibition again Staphylococcus epidermidis bacteria. Antibacterial activity using Mullerr Hilton Agar media in order to have a larger zone of inhibition than using kapok banana starch.